2015
DOI: 10.14257/ijsia.2015.9.1.10
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Implementation of Watermarking Scheme Using XSG

Abstract: Now a day's hardware realization of image processing applications using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…For the time being, hardware realization of OFDM system using Field Programmable Gate Array (FPGA) is an important area of research due to the speed of implementation, low development costs and less time to market with the ability to reduce the complexity and power consumption without sacrificing in the performance of the system [9]. FPGA is truly parallel in nature so different processing operations do not have to compete for the same resources.…”
Section: Abstract-this Article Proposes An Efficient Design and Implementioning
confidence: 99%
See 1 more Smart Citation
“…For the time being, hardware realization of OFDM system using Field Programmable Gate Array (FPGA) is an important area of research due to the speed of implementation, low development costs and less time to market with the ability to reduce the complexity and power consumption without sacrificing in the performance of the system [9]. FPGA is truly parallel in nature so different processing operations do not have to compete for the same resources.…”
Section: Abstract-this Article Proposes An Efficient Design and Implementioning
confidence: 99%
“…Therefore, Hadi et al [8] improved the performance of FT-OFDM system by using Finite Radon Transform (FRAT) as a mapping technique and combined it with FT to produce a new model called as FRAT-FT-OFDM system. In this system, Radon transform was used as a mapping technique instead of conventional mapping techniques such as Quadrature Amplitude Mapping (QAM), and the FT was used to realize the multicarrier modulation instead of FFT or DWT.For the time being, hardware realization of OFDM system using Field Programmable Gate Array (FPGA) is an important area of research due to the speed of implementation, low development costs and less time to market with the ability to reduce the complexity and power consumption without sacrificing in the performance of the system [9]. FPGA is truly parallel in nature so different processing operations do not have to compete for the same resources.…”
mentioning
confidence: 99%
“…The algorithm is prototyped in Virtex-6 (vsx315tff1156-2) FPGA. Real time implementation of Digital Watermarking for Image and Video [4] using DCT domain. The embedding for invisible, semi fragile watermark infortion into compressed video streams using DCT is also worked upon [1].…”
Section: Introductionmentioning
confidence: 99%
“…Xilinx System generator and use of HAAR DWT for watermarking [3] and ML507 Evaluation Platform which is based on the Virtex-5 FPGA using Xilinx System Generator tool [2]. The co-hardware simulation for video watermarking and implementation of design using a Spartan3 device (3S200PQ208) then a Virtex II Pro (xc2vp7-6ff672) [4]. FPGA and ASIC implementation of color image watermarking.…”
Section: Introductionmentioning
confidence: 99%
“…Maity et al [14] suggested a fast Walsh transform (FWT) based on a Spread Spectrum (SS) image watermarking scheme that would serve for authentication in data transmission. In [15], Korrapati Rajitha et al proposed an FPGA implementation of a watermarking system using the Xilinx System Generator (XSG). Insertion and extraction of information were applied in the spatial domain.…”
Section: Introductionmentioning
confidence: 99%